2013
DOI: 10.1177/0886260513506289
|View full text |Cite
|
Sign up to set email alerts
|

“Let’s Get Drunk and Have Sex”

Abstract: Using interviews with 43 college-age individuals, the present study aims to create a more nuanced and complex understanding of the relationship between alcohol and gender in instances of sexual victimization. The existing scholarship suggests that either alcohol or gendered processes are the primary factors in facilitating a sexual assault, one always dominating the other. However, participants express a more complex understanding that suggests that not only do each of these factors contribute individually to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…There were few articles that examined gender norms and other forms of substance use beyond alcohol and tobacco. Those that did were focused on the intersection of sexual/violent behaviors, substance use, and gender norms, not on the direct relationship between gender roles and substance use [48, 49]. There seems to be an emerging trend to examine the role masculinity plays in substance use; however, more research is needed to better understand conflicting findings and extend beyond alcohol and tobacco to other forms of substance use.…”
Section: Gender and Health Behaviorsmentioning
confidence: 99%
“…There were few articles that examined gender norms and other forms of substance use beyond alcohol and tobacco. Those that did were focused on the intersection of sexual/violent behaviors, substance use, and gender norms, not on the direct relationship between gender roles and substance use [48, 49]. There seems to be an emerging trend to examine the role masculinity plays in substance use; however, more research is needed to better understand conflicting findings and extend beyond alcohol and tobacco to other forms of substance use.…”
Section: Gender and Health Behaviorsmentioning
confidence: 99%
“…For example, violence is generally perceived to be masculine and not feminine. Thus, in settings in which men feel they must express their masculinity, or where their masculinity is threatened, acts of violence are accepted as a normative demonstration of masculinity (Cowley, 2014;West & Zimmerman, 1987). Societal expectations for femininity, however, can contribute to society's viewing women's violence toward men as less important or less harmful (Anderson, 2005;Cowley, 2014).…”
Section: Intimate Partner Violence As a Gendered Issuementioning
confidence: 99%
“…Thus, in settings in which men feel they must express their masculinity, or where their masculinity is threatened, acts of violence are accepted as a normative demonstration of masculinity (Cowley, 2014;West & Zimmerman, 1987). Societal expectations for femininity, however, can contribute to society's viewing women's violence toward men as less important or less harmful (Anderson, 2005;Cowley, 2014). Men's and women's interpretation of experiences as a perpetrator or as a victim are informed by the socially constructed and gendered frame of violence, and scholars have called for research that includes male and female perpetrators and victims in order to better understand the nature of gendered violence (Anderson, 2005;Cannon et al, 2015).…”
Section: Intimate Partner Violence As a Gendered Issuementioning
confidence: 99%
“…The beliefs inherent in rape culture are dangerous, as these "social norms" are predictive of men's comprehension of sexual consent, as well as the actual perpetration of sexual assaults (both single and repeat offenses) (Warren, et al, 2015;Zinzow & Thompson, 2015). On college campuses, a widespread social norm regarding rape is that the victim is at least partially responsible if they had consumed alcohol or drugs prior to or during the assault (Cowley, 2014). In fact, recent research has found that over 40% of college students believed that a woman was responsible for being raped if she was intoxicated at the time of the assault (Aronowitz, et al, 2012).…”
Section: Social Normsmentioning
confidence: 99%